Analýza minerálního složení a izotopových poměrů jako součást metabolomických profilů jablek pro jejich autentikaci - Martin Mészáros (VÝZKUMNÝ A ŠLECHTITELSKÝ ÚSTAV OVOCNÁŘSKÝ HOLOVOUSY s.r.o., 2021)
The presented work is focused on the creation and validation of original tools for the detection of apple fruits with false indication of geographical origin by analysing the mineral composition and isotope ratios using the method (ICP-MS) mass spectrometry with inductively coupled plasma. The obtained profiles of the element composition (P, K, Mg, Fe, Cu a Zn) and isotope ratios (86Sr/87Sr a 10B/11B) of individual samples were statistically processed using principal component analysis (PCA). The achieved results of the analysis of the mineral composition and isotope ratios of Polish and Czech apples show different trends, especially for the elements P, Cu and for the isotope ratio of 10B/11B. However, these trends alone do not yet allow for a sufficient distinction among the geographical origin of apples. These trends were not statistically detected for other analysed elements and for the isotope ratio 86Sr/87Sr. Therefore, in the future we plan to perform a combined multidimensional analysis with other methods, such as the evaluation of selected phenolic metabolites in the fruit flesh.